Is grip strength a marker for cognitive function, neurodegeneration, and resilience? - Alexander Ivan B. Posis; Hilary L. Colbeth; Mihika S. Deshpande; Kristen M. George; Batool Rizvi; Rifat B. Alam; Ruijia Chen; Dan M. Mungas; Paola Gilsanz; María M. Corrada; Rachel A. Whitmer (GeroScience, 2025)
Assessing whether grip strength is associated with cognitive decline and brain health could help identify a target to prevent or delay cognitive impairment. Therefore, we tested whether grip strength is associated with brain health as indicated by magnetic resonance imaging and domain specific cognitive decline. We also assessed whether grip strength was a cognitive resilience proxy using moderation tests. This study included cognitive and neuroimaging data from 861 participants in three harmonized cohorts. We fit multivariable linear mixed-effects and linear regression models to test associations between grip strength, neuroimaging markers, and cognition. We also tested moderation by gender and age. Greater grip strength was associated with slower verbal episodic memory decline and greater total gray matter volume. Associations of grip strength with executive function, total hippocampal volume, and white matter hyperintensities were not significant, but in the expected direction. Age moderated associations of grip strength and white matter hyperintensities. Grip strength was a significant proxy for cognitive resilience related to white matter hyperintensity volume and verbal episodic memory decline only. Future research should examine other measures of physical performance that are associated with later-life cognitive and brain health.